1985
DOI: 10.2307/3430070
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis of Environmental Agents: Use of X-Ray Crystallographic Data to Determine Molecular Reactivity

Abstract: This paper explores the use of crystallographic techniques as an aid in understanding the molecular reactivities of a number of agents that are of concern to pharmacologists and toxicologists. The selected examples demonstrate the role of structural data in the determination of absolute configuration, configurational flexibility and active-site topology for a reactive species. For example, the role of absolute stereochemistry in understanding synthetic pyrethroid structure-activity relationships is shown from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…2), Additional industrial chemicals such as chlorophenoxy acids (Table 1, group 2) and nitrophenols (Table 1, group 3) were also effective competitors for the T4 binding site. Theoretical modelling studies by Cody (1985) have suggested potential fitting of chlorophenoxy acids in the binding pocket of transthyretin. Little is known about in vivo effects of chlorophenoxy acids and nitrophenols with respect to thyroid hormone levels in man or experimental animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2), Additional industrial chemicals such as chlorophenoxy acids (Table 1, group 2) and nitrophenols (Table 1, group 3) were also effective competitors for the T4 binding site. Theoretical modelling studies by Cody (1985) have suggested potential fitting of chlorophenoxy acids in the binding pocket of transthyretin. Little is known about in vivo effects of chlorophenoxy acids and nitrophenols with respect to thyroid hormone levels in man or experimental animals.…”
Section: Resultsmentioning
confidence: 99%
“…Modelling studies also indicate a fit of DDT in the T4 binding pocket of transthyretin (Cody 1985). The thyroid hormone-lowering effect of DDT, the parent compound, in a few experimental animals systems is well known (Bastomski 1974;Hurst et al 1974).…”
Section: -Sec-butylphenol (Dinoseb)mentioning
confidence: 99%